Correlações e interações de longo alcance em meios desordenados: linhas costeiras e transição de Anderson - Morais, Pablo Abreu de (2012)
Many physical phenomena have strong dependence on the disorder of the medium in which they occur. The {it Anderson} theory localization, for example, states that the introduction of disorder in electronic systems can promote the metal-insulator transition, also known as {it Anderson} transition. However, for low dimensional systems, according to the same theory, any finite degree of uncorrelated disorder is able to promote the exponential localization of all electronic functions. The general {it Anderson} theory localization is violated when long-range correlations and long-range interactions are used. In this scenario, the metal-insulator transition also occurs for low dimensional systems. In network problems, the long-range connections are responsible for the short average distance between individuals belonging to the same social network. This phenomenon is popularly known as six degrees of separation. Furthermore, {it Kleinberg} showed that the introduction of a power-law distribution of long-range links in a network produces a minimum in the transmission time information from a source site to a target site network . In this thesis, we investigate how the long-range disorder changes the universality class of two mathematical models that represent the following physical problems: the erosion process in correlated landscapes and the delocalization-localization transition of the normal modes of a harmonic chain with long range connections restricted by a cost function. In the first model, we show that long-range spatial correlations in the geological properties of the coast, in the critical regime of our model, generates a spectrum of fractals shorelines whose fractal dimensions vary between {it D} = 1.33 and 1.00 when we vary the {it Hurst} exponent in the range $0< H <1$. Furthermore, when we use uncorrelated surfaces, the shoreline, for very intense sea erosion, are self-affine and belong to the same universality class of the interfaces described by the equation of {it Kardar-Parisi-Zhang} ({it KPZ}). In the second model, we show that long-range links in a chain harmonic inserted with a probability with decreasing size of the bond, $p sim r^{-alpha}$, restricted by a cost function proportional to chain length, promotes a delocalization-localization transition of the normal modes for the exponent $ alpha simeq 1.25$.